Pengaruh Pemahaman Saham Syariah Dan Perilaku Keuangan Mahasiswa FEBI UIN STS Jambi Terhadap Minat Pembelian Saham Syariah Melalui PT FAC Sekuritas - Najuwanda. R; Eja Armaz Hardi; Agusriandi Agusriandi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This study aims to determine and analyze the influence of Islamic stock understanding and financial behavior on the intention to purchase Islamic stocks at PT FAC Sekuritas. The method used in this study is a quantitative method, and the data analysis method used is the coefficient of determination test. The sample in this study was 94 samples of FEBI students at UIN STS Jambi class of 2019-2021, by distributing Likert scale questionnaires. The results of the study show that understanding of Islamic stocks (X1) has a significant positive effect on the intention to purchase Islamic stocks (Y). This is evidenced by the value of Tcount 4.379 > Ttable 1.661 and a Sig value of 0.001 <0.05, which means that Ho is rejected and Ha is accepted. Financial Behavior (X2) shows that there is a significant positive influence on the intention to purchase Islamic stocks (Y). This is evidenced by the tcount value of the minimum capital variable of 3.480 > 1.661 with a significance value of 0.001 <0.05, so it can be concluded that Ha is accepted and Ho is rejected. Understanding of sharia stocks and financial behavior together have a significant effect on the intention to buy sharia stocks. It is known that the significance values ​​for (X1) and (X2) simultaneously affect (Y) of 0.000 <0.005 and the value of Fcount > Ftable (34.631 > 3.10). So it can be concluded that Ha is accepted and H0 is rejected. This means that the higher the level of understanding of Islamic stocks and the better financial behavior, the higher the interest of students in purchasing Islamic stocks at PT FAC Sekuritas.